Nonverbal cues to deception: insights from a mock crime scenario in a Chinese sample - Li, He; Song, Hu; Li, Menghan; Li, Hanxue (Frontiers in Psychology, 2024)
Nonverbal behaviors could play a crucial role in detecting deception, yet existing studies on deception cues have largely centered on Western populations, predominantly university students, thus neglecting the influence of cultural and sample diversity. To address this gap, our study explored deception cues within an Asian cultural setting, utilizing a mock crime paradigm. Our sample comprised Chinese participants, including both men and women with various socioeconomic status (SES) backgrounds. Our findings revealed that compared to truth tellers, liars exhibited heightened emotions and an increased cognitive load. Furthermore, liars showed a higher frequency of self-adaptors and a longer duration of gaze aversion. Our findings contribute to a more profound understanding of deception cues within Asian culture and have implications for practical fields such as criminal interrogation.